(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Developing technical thinking is a key educational objective in modern engineering education. Technical thinking refers to the system of intellectual operations that allow an engineer to analyze problems, visualize mechanisms, construct models, and apply theoretical knowledge to practical design and production tasks. However, in many engineering programs, students acquire theoretical knowledge without developing this crucial mode of thought. This study explores effective pedagogical methods for developing technical thinking among undergraduate engineering students through problem-based, project-based, and model-based approaches. Integrating modeling, visualization, and real-world problem tasks effectively develops technical thinking. Engineering curricula should embed these methods throughout the learning process, combining theory with creative practice to produce technically competent graduates.